THE LEGAL OBLIGATIONS OF A NEW EU MEMBER STATE - Christen Boye Jacobsen (Romanian Journal of European Affairs, 2004)
The article is centered around three assumptions:First, that the acquis communautaire, as defined by the accession acts, comprises about 20 categories and thus many more categories than the treaties, directives, and regulations.Second, the duties under the Copenhagen Criteria comprise much more than implementation of the acquis. It implies the accession to a large number of international treaties, and the introduction of law in areas where the EU has no competence such as bankruptcy, criminal law, and land registration, and the introduction of general legal reforms. This is required to meet the implicit requirement on democracy, rule of law and a modern (West-European) market economy and infrastructure.Third, it is necessary to take an interest in the whole legal structures, which add up to much more than the sum of normative acts, including the basic theoretical training which the universities give under the normal law studies.